Summary of the N1-P2 Cortical Auditory Evoked Potential to Estimate the Auditory Threshold in Adults - Lightfoot, Guy (Seminars in Hearing, 2016)
This article introduces the cortical auditory evoked potential (CAEP) and describes the use of the N1-P2 response complex as an objective predictor of hearing threshold in adults and older children. The generators of the CAEP are discussed together with issues of maturation, subject factors, and stimuli and recording parameters for use in the clinic. The basic methods for response identification are outlined and suggestions are made for determining the CAEP threshold. Clinical applications are introduced and the accuracy of the CAEP as an estimator of hearing threshold is given. Finally, a case study provides an example of the technique in the context of medicolegal assessment.
Keywords: Cortical evoked response; hearing threshold; nonorganic hearing loss; N1-P2